A Case Study on Student Club Information System Development at Nabon Islam Education Foundation School - Lamsub, Dinat (Journal of Science and Technology Songkhla Rajabhat University, 2020)
This research aims to develop the Student Club Information System at Nabon Islam Education Foundation School for data management instead of document system. The system was developed as a web application for the users, namely students, advisors and staff to be able to use the system easily and effectively. The students were given the right to choose which club they were interested to apply in. The advisors quickly and accurately recorded and validated the data. Also, the staff quickly and accurately managed basic information. The programming language used to develop system were PHP, and MySQL was used as database management system. The result shows that the users’ satisfaction was at very good level ( = 4.53). In conclusion, this application increases information management efficiency of the student club.